(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
In part II of this series, it was reported that the solar home system (SHS) supplied by REB in some islands of the Meghna river in the district of Narsingdi could not meet the demand of the recipients in the rainy season when the sky remained overcast with cloud. The tilt angle for all installations was 45° facing south. In this study, effects of direct and diffuse sunlight with variation of tilt angles from 0° to 45° were studied using a mono crystalline silicon cell. Pyranometer and the solar panel were kept under identical conditions. Energy absorbed by the solar panel in diffuse sunlight was found 0.55% of that received by the Pyranometer under similar conditions showing that mono crystalline silicon solar cell of the type under study was not suitable for use in SHS. Moreover, the gap between the panel and the solid surface below it has significant effects on the efficiency of the solar cell. Further similar study using different kinds of cells- mono crystalline, poly crystalline and amorphous is needed for proper designs of SHS. Optimization of the gap between the panel and the solid surface below it is important for roof-mounted and ground-mounted panels. Key words: Silicon solar cells; Tilt angle; Diffuse light; Home lighting; Monocrystaline. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8114 Bangladesh J. Sci. Ind. Res. 46(1), 117-122, 2011